2005
DOI: 10.1161/01.cir.0000155615.68924.b3
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Cardiac Parvovirus B19 Infection in Patients With Isolated Left Ventricular Diastolic Dysfunction

Abstract: Background-The etiology of left ventricular (LV) isolated diastolic dysfunction often remains unclear. In the present study, we report a strong association between parvovirus B19 (PVB19) genomes and isolated LV diastolic dysfunction. Methods and Results-In 70 patients (meanϮSD age, 43Ϯ11 years) admitted with exertional dyspnea and/or reduced exercise tolerance despite preserved LV systolic contractility (ejection fractionϭ68%), isolated diastolic dysfunction was clinically suspected. Patients with classic risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(142 citation statements)
references
References 37 publications
10
122
2
8
Order By: Relevance
“…Conversely, physical exercise, which improves endothelial dysfunction, was found to preserve LV compliance in elderly athletes compared to sedentary seniors [65]. As a result of coronary microvascular endothelial inflammation, the vasodilator response of the coronary microvascular bed to acetylcholine was reduced in HFpEF, which correlated with diastolic LV dysfunction [66]. Similar paracrine endocardialmyocardial interactions have previously already been reported [67].…”
Section: Increased Agesupporting
confidence: 66%
“…Conversely, physical exercise, which improves endothelial dysfunction, was found to preserve LV compliance in elderly athletes compared to sedentary seniors [65]. As a result of coronary microvascular endothelial inflammation, the vasodilator response of the coronary microvascular bed to acetylcholine was reduced in HFpEF, which correlated with diastolic LV dysfunction [66]. Similar paracrine endocardialmyocardial interactions have previously already been reported [67].…”
Section: Increased Agesupporting
confidence: 66%
“…14 MC caused by infection with human parvovirus B19 (PV-B19) has been reported in infants with MC, 15 and the PV B19 genome was predominant in patients with unexplained isolated diastolic ventricular dysfunction. 16 PV-B19 is associated Table 2. SAJI T et al…”
Section: Discussionmentioning
confidence: 99%
“…Some studies support that viral infections would be related to the development of myocarditis and idiopathic dilated cardiomyopathy (IDCM), suggesting that the IDCM would be a result of a previous subclinical myocarditis. The viral infection has also been related with restrictive cardiomyopathy, as demonstrated by Tschope, Bock C-T et al in study with 70 patients that showed strong association between parvovirus B19 and isolated left ventricular diastolic dysfunction [12].…”
Section: Discussionmentioning
confidence: 86%